Utilization and outcomes of aortic valve replacements (from the United States readmissions database) - Shashank Shekhar; Abhishek Ajay; Toshiaki Isogai; Roop Kaw; Anas Saad; Ankit Agrawal; Hassan Lak; Tikal Kansara; Amgad Mentias; Amar Krishnaswamy; Lars Svensson; Samir R. Kapadia (American Heart Journal Plus, 2022)
Study objective: Assess the utilization of aortic valve replacements (AVR). Design: Retrospective analysis of the Nationwide Readmissions Database (2016–2018). Setting: Nationwide. Participants: Heart failure patients with concomitant aortic stenosis (CHF + AS cohort) or aortic stenosis with aortic regurgitation (CHF + AS+AR cohort). Interventions: Transcatheter aortic valve implantation (TAVI), surgical aortic valve replacement (SAVR), no-AVR. Main outcome measures: Utilization of treatment interventions. Results: In the CHF + AS cohort, TAVI, SAVR and no-AVR were done in 9.3 %, 10.8 % and 79.9 % of patients respectively. Similarly, majority of CHF + AS+AR patients were managed with no-AVR (53.2 %). Of patients managed with no-AVR in the first six months of each year, only 7.9 % of CHF + AS and 11.8 % of CHF + AS+AR patients underwent AVR in the subsequent six months of the year. No-AVR patients had worse short-term outcomes in comparison to AVR recipients. Conclusion: More studies are needed to understand the timing, indications and utilization of AVR in this population.